GIS-BIM Based Regional Seismic Risk Assessment for Dubai, UAE - Maky, Ahmed Mansour (2023)
A Master of Science thesis in Civil Engineering by Ahmed Mansour Maky entitled, “GIS-BIM Based Regional Seismic Risk Assessment for Dubai, UAE”, submitted in May 2023. Thesis advisor is Dr. Mohammad AlHamaydeh and thesis co-advisor is Dr. Ahmed El-Kady. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).